Frequency of Vitamin D Deficiency among Patients Presenting with Stroke - Amir Taj Khan, Kalim Ullah Khan, Muhammad Ishfaq, Naveed Ahmad, Muhammad Khalid, Muhammad Zubair Khan, Izhar Ahmad, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Stroke is the leading cause of both mortality and disability on a global scale. The documented incidence of cerebral hemorrhages at Pakistan's CT scan facilities varies from 31-40% of cases, whereas ischemic stroke is claimed to be responsible for 60-90% of cases Objectives: The objective of the study was to assess the prevalence of vitamin D deficiency in patients presenting with stroke Methodology: The current study was descriptive and cross-sectional carried out at the Medicine Department, Hayatabad Medical Complex Peshawar for duration of six months February 2018 to August 2018. Patients were enrolled from both the emergency and accident department and outpatient department. The blood samples were taken and transferred to the hospital diagnostic laboratory for the assessment of deficiency of vitamin D in serum. The data analysis was done by using IBM SPSS version 16. Results: In this study, totally 341 patients were enrolled. There were 239 (70.09%) male patients while female patients were 102 (29.91%). The vitamin D deficiency in serum was observed in 50.1% patients. Conclusion: Stroke is still a calamity, and vitamin D could have played pivotal role in the pathogenesis of stroke. Since most of our population is already deficiency in 25-hydroxyvitamin D, therefore, relationship between stroke and vitamin D deficiency cannot be studied at hospital settings. We recommend more analytical research projects not only at hospital level but also at community level to draw conclusions about the relationship between vitamin D status and occurrence of stroke. Keywords: Stroke, Cerebrovascular accident, acute ischemic stroke, hypertension, vitamin D, 25-hydroxyvitamin D